African and Western Concepts of Spirituality and the Transcendence of God: A Case Study of Sub-Sahara African Christians in Finland - Banyanga, Jean Nubaha (International Journal of Culture and Religious Studies, 2023)
Purpose: Through evangelism and missionary activities, Western Christian spirituality influences the lives of many people, both individually and collectively, and in many cultures around the world including the Sub-Sahara African region. This article aims to examine spirituality and the various ways in which to recognize it from the perspectives of both Sub-Sahara African and Western concepts. It also examines the secularization of Finnish churches and how this shapes the spirituality of Christians originating from Sub-Saharan Africa living in Finland. Methodology: The argument is presented through an analysis of existing literature and documents on the matter. Findings: The findings show that secularization had negative consequence to many churches in the Western countries. Consequently, Sub-Sahara African Christians are setting up their own ecclesiastic congregations in many cities of Finland. Unique Contribution to Theory, Policy and Practice: It is therefore important for individuals to belong to groups where the numbers share visible characteristics, values, and convictions.